The effectiveness of a teaching model based on self - regulated learningon developing self- regulated learning skills, teaching skills and reducing teaching anxiety amonggeneral diploma English students - Hussien, Hanan Ahmed (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2016)
هدف البحث الحالي لتحديد فاعلية نموذج تدريسي قائم على التعلم المنظم ذاتيا في تنمية مهارات التنظيم الذاتي ومهارات التدريس وخفض قلق التدريس لدى طلاب الدبلوم العام تخصص لغة انجليزيه) نظام العام الواحد (، وحددت أسس بناء النموذج ووضع تصور لمراحله وإجراءاته، وفي ضوءه اعد دليل للمعلم وأوراق عمل للطالب، كما اعد مقياس التنظيم الذاتي واختبار تحصيل مهارات التدريس ومقياس قلق التدريس، واختيرت مجموعة البحث من طلاب الدبلوم العام-نظام العام الواحد كمجموعه تجريبيه واحده. وطبقت أدوات البحث على المجموعة التجريبية قبليا وثم تم تدريس المهارات التدريسية باستخدام النموذج التدريسي المقترح، ثم طبقت أدوات البحث على المجموعة التجريبية بعديا. أثبتت نتائج البحث فاعلية النموذج التدريسي المقترح في تنمية مهارات التنظيم الذاتي للتعلم ومهارات التدريس المختارة وخفض مستوى القلق التدريسي لدى طلاب المجموعة التجريبية.
The objective of this research was to determine the effectiveness of a self- regulated learning model in developing the self-regulated skills, teaching skills and reducing teaching anxiety among general diploma students. The basics upon which this model was built were determined, the teacher’s guide and the student’s worksheet were prepared. A self- regulation skills questionnaire, teaching skills achievement test and teaching anxiety scale were prepared as well. The Study had one experimental group (one-year general diploma English students). The tools of the study were pre applied on the experimental group. Teaching skills were introduced according to the suggested teaching model. The tools were post applied on the experimental group. The statistical analysis of the results proved the effectiveness of the suggested self- regulated learning model in developing the skills of self-regulatory learning ,teaching skills and reducing the teaching anxiety level of the experimental group.
Keywords: مهارات التدريس -- طرق التدريس -- تطوير الذات -- تدريس اللغة الإنجليزية